2019
DOI: 10.1111/jce.13898
|View full text |Cite
|
Sign up to set email alerts
|

How to implant a phrenic nerve stimulator for treatment of central sleep apnea?

Abstract: Background Central sleep apnea (CSA) is a breathing disorder caused by the intermittent absence of central respiratory drive. Transvenous phrenic nerve stimulation is a new therapeutic option, recently approved by the FDA , for the treatment of CSA. Objective To describe the technique used to implant the transvenous phrenic nerve stimulation system (the remedē System, Respicardia, Inc). Methods The remedē System is placed in the pectoral region, typically on the right side. A single stimulation lead is placed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…The median ESS at baseline and 5-years were 9 [5,14] and 6 [4,11], respectively (Table 2), demonstrating a consistent and clinically meaningful ≥3 point reduction 18,19…”
Section: Daytime Sleepinessmentioning
confidence: 93%
See 1 more Smart Citation
“…The median ESS at baseline and 5-years were 9 [5,14] and 6 [4,11], respectively (Table 2), demonstrating a consistent and clinically meaningful ≥3 point reduction 18,19…”
Section: Daytime Sleepinessmentioning
confidence: 93%
“…9,10 The TPNS system (Supplement Figure 1) is an implantable neurostimulation device consisting of a pulse generator implanted in the pectoral region, a stimulation lead placed in either the left pericardiophrenic or right brachiocephalic vein, and an optional sensing lead placed in the azygos vein. 11 The TPNS device automatically delivers therapy, continuously throughout the night during the scheduled time when the patient is in a sleeping position and at rest, without requiring patients to manually activate therapy. 12 As a condition of FDA approval, the Post Approval Study (PAS) collected evidence regarding long-term safety and effectiveness in adult subjects with moderate to severe CSA.…”
Section: Introductionmentioning
confidence: 99%
“…A Biotronik Lumax 340 CRTD device was implanted 32 months before the TPNS device in the left pectoral region with transvenously placed right atrial, right ventricular dual shock coil, and bipolar coronary sinus leads. The initial TPNS device implantation was performed in the right pectoral area as previously described 7 . TPNS stimulation lead (respistim LQS, Model 4055; Respicardia Inc.) was positioned within the left PPV (Figure 1) and electrical testing revealed desired and effective phrenic nerve stimulation.…”
Section: Case Reportmentioning
confidence: 99%
“…From this transvenous position, the phrenic nerve can be stimulated 6,9 . Recently, Fox et al 6‐8,10 demonstrated long‐term efficacy and safety of TPNS 3 years postimplant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation